ENERGY ASPECTS OF STEELMAKING SLAGS APPLICATION IN METALLURGY - V. L. Naydek; V. I. Kurpas; S. G. Melnik (Литьë и металлургия)
A comparative assessment of energy intensity of converter steel production in different types of smelting with slag processing in the ladle was made. Analysis of the data shows that the use of liquid steel slag in steel production for its refining saves about 2.2 GJ or 75 kg of coal equivalent for each ton of metal.